NEEDS ANALYSIS FOR ENGLISH DISCOURSE TEXTBOOKS EVALUATION FOR INDONESIAN STUDENTS: GRADUATE STUDENTS’ PERCEPTION - Badi’atul Azmina; Dyah Fitri Mulati; Khotimah Mahmudah; admin, admin (Universitas Aisyah Pringsewu, 2024)
This study aims to uncover the perceptions of graduate students on the content, examples, exercises/tasks, and presentation/format of the textbook